1983
DOI: 10.1038/jcbfm.1983.57
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Positron Emission Transaxial Tomography Evaluations of Normal Aging and Alzheimer's Disease

Abstract: Summary: Young normal subjects, old normal subjects, and patients with senile dementia of the Alzheimer's type (SDAT) were studied with both computed tomography (CT) and positron emission transaxial tomography (PETT). Increases in ventricular size with both aging and disease were measured. Regional glucose metabolic rate was not affected by age, but was markedly reduced in SDAT pa tients. These data indicate that in normal aging, structural brain changes may be more salient than biochemical Abbreviations used:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(57 citation statements)
references
References 21 publications
4
53
0
Order By: Relevance
“…The substantial decrease in glucose utilization and oxygen consumption in both AD and VaD brains is well established [83][84][85][86][87][88][89][90][91][92]. In agreement with CBF findings, positron emission tomography studies have revealed that reduced regional metabolic rates of glucose in the mesial temporal lobe structures is present in early AD, and correlates with the severity of dementia [84,[87][88][89].…”
Section: Differential Diagnosis Of Ad and Vad: The Contribution Of Nesupporting
confidence: 65%
“…The substantial decrease in glucose utilization and oxygen consumption in both AD and VaD brains is well established [83][84][85][86][87][88][89][90][91][92]. In agreement with CBF findings, positron emission tomography studies have revealed that reduced regional metabolic rates of glucose in the mesial temporal lobe structures is present in early AD, and correlates with the severity of dementia [84,[87][88][89].…”
Section: Differential Diagnosis Of Ad and Vad: The Contribution Of Nesupporting
confidence: 65%
“…The authors concluded that their findings supported the premise that cerebral metabolic patterns can be dis tinctive among normal, depressed, and demented elderly persons. In an investigation also using the combined methods of CT and PET with 18 PDG, de Leon et al (1983) advanced the notion that in the normal aged (mean age 67 years), structural brain changes (reflected by ventricle-to-brain ratios in CT scans) may be more salient than biochemical changes evidenced by PET, and that although both occurred in patients with senile dementia of the Alz heimer type (mean age 73 years), the biochemical changes were more marked. On the whole, they did not find changes in glucose metabolism in normal aging, and consider these findings consistent with other investigations on oxygen metabolism in the normal aged.…”
Section: Organization Of Behavior (Adaptation)-disturbed (Organiza Timentioning
confidence: 99%
“…Such human studies, however, cannot exclude the possibility of underlying disease pathology for which clinical symptoms have not yet emerged. Brain regions, including parietotemporal and frontal association areas, that show prominent cerebral metabolic reductions in Alzheimer's disease (AD) with functional neuroimaging (Frackowiak et al, 1981;de Leon et al, 1983;Duara et al, 1986;Silverman et al, 2001;Alexander et al, 2002) also show decrements in individuals without clinical symptoms but with increased genetic risk for AD (Reiman et al, 1996(Reiman et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%